KLASIFIKASI EMOSI DALAM LANGGAM-LANGGAM KARYA KI WIDODO BROTOSEJATI: KAJIAN PSIKOLOGI SASTRA DAVID KRECH - Umi Endah Nur Aini; Zustiyantoro, Dhoni (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study explores how the classification of emotions in the twelve styles of Ki Widodo Brotosejati's work according to David Krech's psychology and its relevance to Javanese culture. The approach used is a literary psychology approach with David Krech's emotion classification theory which classifies emotions into four types, including basic emotions (ED), emotions related to stimulus sensors (ESS), emotions related to self-assessment (EPD), and emotions related to others (EO). The research method used is a qualitative method. The researcher collected data using literature study techniques, heuristic reading, and hermeneutics. The results of this study found 24 data in the form of lyric quotations by Ki Widodo Brotosejati. It consisted of 15 basic emotional data, 2 emotional data related to stimulus sensors, 3 emotional data related to self-assessment, and 4 emotional data related to others. The dominant emotion is the basic emotion of sadness which amounted to 8 citation data.